2004
DOI: 10.1111/j.1365-201x.2004.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood pressure and carotid baroreflex function during arm and combined arm and leg exercise in humans

Abstract: These findings demonstrate that during combined arm and leg and exercise in the upright position the CBR resets to a lower blood pressure than during arm cranking likely because the central blood volume is enhanced by the muscle pump of the legs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 43 publications
0
37
1
Order By: Relevance
“…Indeed, cardiopulmonary baroreceptor loading may exert a central inhibitory effect during sympatho-excitatory maneuvers, such as carotid baroreceptor unloading or exercise. However, as cardiopulmonary baroreceptor loading during exercise is strongly associated with an attenuated carotid baroreflex resetting (36,48), it is unlikely that this would explain the age-related relocation of the operating point observed in the present study, as we observed an augmented carotid baroreflex resetting in older individuals. Further studies are needed to determine the mechanisms underlying the age-related attenuation in the BP responses to carotid baroreflex unloading during exercise.…”
Section: Discussioncontrasting
confidence: 42%
“…Indeed, cardiopulmonary baroreceptor loading may exert a central inhibitory effect during sympatho-excitatory maneuvers, such as carotid baroreceptor unloading or exercise. However, as cardiopulmonary baroreceptor loading during exercise is strongly associated with an attenuated carotid baroreflex resetting (36,48), it is unlikely that this would explain the age-related relocation of the operating point observed in the present study, as we observed an augmented carotid baroreflex resetting in older individuals. Further studies are needed to determine the mechanisms underlying the age-related attenuation in the BP responses to carotid baroreflex unloading during exercise.…”
Section: Discussioncontrasting
confidence: 42%
“…In resting and exercising humans, increases in CBV can be accomplished by changing the posture from upright to supine (107), by infusion of serum albumin (79,81) or infusion of a blood volume expander, such as low molecular weight dextran, and by increases in pedal frequency, for example, from 60 to 80 rpm at the same oxygen uptake (81). Decreases in CBV during rest and exercise can be accomplished by changing posture from supine to upright (81) and using lower body negative pressure (78,79).…”
Section: Arterial Baroreflexmentioning
confidence: 99%
“…To avoid this problem, Thr and Sat have been defined as the values of X at which Y is below or above the upper and lower plateau values of Y, respectively, by some arbitrary small value. Very commonly (see, e.g., 12,[17][18][19][20][21][22][23]28), this arbitrary value is taken as 5% of the response range for Y, and we shall follow this convention here.Many authors have used an equation derived by Chen and Chang (2) to calculate Thr and Sat, as follows:It is commonly stated (see, e.g., 12,[17][18][19][20][21][22][23]28) that the values of Thr and Sat calculated according to Eqs. 3 and 4 are the values of X at which the corresponding Y values are 5% (of the response range) below and above the upper and lower plateau values of Y, respectively.…”
mentioning
confidence: 99%
“…To avoid this problem, Thr and Sat have been defined as the values of X at which Y is below or above the upper and lower plateau values of Y, respectively, by some arbitrary small value. Very commonly (see, e.g., 12,[17][18][19][20][21][22][23]28), this arbitrary value is taken as 5% of the response range for Y, and we shall follow this convention here.…”
mentioning
confidence: 99%
See 1 more Smart Citation